Cultural Contents on New Step-Up: Reading and Writing for University Students - Yuliana Zakiyah; Dwi Rukmini (Universitas Negeri Semarang, 2022)
EFL coursebooks still become an essential teaching medium for teachers and a primary learning source for students. This research aims at identifying the kinds of source culture and themes of culture in the reading texts, reading exercises, and writing exercises. The method used in this research was qualitative with content analysis. The textbook contains 14 chapters, divided into two subject materials. There were seven units for reading materials and seven units for writing materials. The analysis found that the international target culture and small â€œcâ€ culture was dominantly presented in the reading texts. Another result showed that the small â€œcâ€ culture was dominantly presented in the reading exercises. The last result revealed that the cultural contents were used in each unit of the writing exercises. Based on the research findings, it is suggested that the reading passages and reading exercises in the textbook should be developed more in terms of kinds of source culture and themes of culture. Also, English materials developers, especially the authors should include more source culture particularly in reading passages and reading exercises. Finally, it can be inferred that the textbook can be used as one of the learning sources in Islamic University.